Return to Sport After Anterior Cruciate Ligament Injury: Panther Symposium ACL Injury Return to Sport Consensus Group. Issue 6 (29th June 2020) - Meredith, Sean J.; Rauer, Thomas; Chmielewski, Terese L.; Fink, Christian; Diermeier, Theresa; Rothrauff, Benjamin B.; Svantesson, Eleonor; Hamrin Senorski, Eric; Hewett, Timothy E.; Sherman, Seth L.; Lesniak, Bryson P.; ,; et al.
Background: A precise and consistent definition of return to sport (RTS) after anterior cruciate ligament (ACL) injury is lacking, and there is controversy surrounding the process of returning patients to sport and their previous activity level. Purpose: The aim of the Panther Symposium ACL Injury Return to Sport Consensus Group was to provide a clear definition of RTS after ACL injury and a description of the RTS continuum as well as provide clinical guidance on RTS testing and decision-making. Study Design: Consensus statement. Methods: An international, multidisciplinary group of ACL experts convened as part of a consensus meeting. Consensus statements were developed using a modified Delphi method. Literature review was performed to report the supporting evidence. Results: Key points include that RTS is characterized by achievement of the preinjury level of sport and involves a criteria-based progression from return to participation to RTS and, ultimately, return to performance. Purely time-based RTS decision-making should be abandoned. Progression occurs along an RTS continuum, with decision-making by a multidisciplinary group that incorporates objective physical examination data and validated and peer-reviewed RTS tests, which should involve functional assessment as well as psychological readiness. Consideration should be given to biological healing, contextual factors, and concomitant injuries. Conclusion: The resultant consensus statements and scientific rationale aim to inform the reader of the complex process of RTS after ACL injury that occurs along a dynamic continuum. Research is needed to determine the ideal RTS test battery, the best implementation of psychological readiness testing, and methods for the biological assessment of healing and recovery.